Kadar IgG serum pada bayi yang diimunisasi dengan vaksin campak setelah pemberian suplemen vitamin a (Studi di Kabupaten Temanggung, Jawa Tengah=Serum IgG Level in the Immunized Babies with Measles Vaccin Following ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Measles is still a public health problem in Indonesia. Although the Universal Child Immunization (UCI) has been reached, in several districts measles outbreaks still exist. In Temanggung Regency, Central Java, measles is still high in number although measles immunization coverage has reached 96%. This study was aimed investigate the effects of vitamin A supplementation on IgG antibody titer of the babies immunized with measles vaccin, and to examine whether the nutritional status influenced the effect of vitamin A supplementation on antibody titer. This study was a quasi-experimental study using pre-test-post-test control group design and was carried out from November 2000 until February 2001. The subjects were 104 babies of 9-11 months consisted of intervention group with vitamin A (n=52) and the control group without vitamin A (n=52). Each children in the vitamin A group was given 100.000 IU of vitamin A per oral before measles immunization, when the babies were 6 months or 3 months before immunization (n=26) and 1 week before measles immunization was given (n=26). The independent variable was vitamin A supplementation, while the dependent variable was antibody level post measles immunization. The serum IgG antibody titer was determined by ELISA Technique. The vitamin A supplementation before measles immunization resulted in higher IgG antibody level one month post immunization compared with that without vitamin A, and was statistically significant p